Fading Utopias: The Critical Unveiling of Revolutionary Ideals in Cuban Speculative Cinema - Juan-Navarro, Santiago (Recent Research Advances in Arts and Social Studies Vol. 7, 2024)
This study investigates the transition from idealistic aspirations to disillusioned outcomes in Cuban cinema after the pivotal 1959 revolution led by Fidel Castro, an event that significantly shaped the 20th-century socio-political discourse. Like the Russian and Mexican revolutions before it, the Cuban revolution initially aimed at establishing social justice and prosperity. However, despite its early promise and international attention, the revolution's journey from a beacon of utopian hope to a landscape marked by dystopian disillusionment reflects the complex interplay of internal and external pressures, including autocratic governance and socio-economic challenges. This narrative shift is evident in the Cuban cinematic realm, particularly through films like Alejandro Brugués’ Juan de los Muertos (2011), Tomás Piard’s Los desastres de la Guerra (2012), Eduardo del Llano’s Omega 3 (2014), Rafael Ramírez’s Diario de la niebla (2016), Yimit Ramírez’s Gloria eterna (2017), Alejandro Alonso’s El Proyecto (2017), and Miguel Coyula’s Corazón Azul (2021), which collectively explore the dystopian reality of post-revolutionary Cuba. Utilizing a qualitative content analysis informed by M. Keith Booker's conceptualization of dystopia a narrative form that critiques societal structures and political systems, this research examines the thematic and aesthetic elements of selected Cuban films to delve into their reflections on the nation's socio-political evolution. By situating these cinematic works within the broader Cuban socio-political narrative, the study reveals how speculative fiction in cinema acts as a pivotal lens, scrutinizing the unfulfilled aspirations of the Cuban revolution and its dystopian consequences. This methodological approach not only sheds light on the disillusionment with the revolutionary endeavour but also emphasizes cinema’s significant role in navigating the intricate dynamics between utopian aspirations and dystopian realities in Cuba.